2017
DOI: 10.1002/ptr.5981
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Iris tenuifolia extract reduces brain damage in a mouse model of cerebral ischaemia

Abstract: In the previous experiments, the neuroprotective role of Iris tenuifolia Pall. (IT) in the model of middle cerebral artery occlusion (MCAO) was investigated. In addition, the concentrations of the cytokines tumour necrosis factor-alpha and interleukin-6 in blood plasma were measured. It was found that IT administered 1 hr prior to MCAO or immediately after MCAO reduced infarct volume significantly. IT application 1 and 4 hr after MCAO, respectively, was without any effect on infarct volume. There were no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Similarly, the in vivo neuroprotective potential of I. tenuifolia Pall ethanolic extract was evaluated for the first time in a middle cerebral artery occlusion model (MCAO) using C57BL/6J mice [152]. Accordingly, the applications of I. tenuifolia Pall ethanolic extract one hour before or immediately after the surgery outstandingly decreased the infarct size.…”
Section: Neuroprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the in vivo neuroprotective potential of I. tenuifolia Pall ethanolic extract was evaluated for the first time in a middle cerebral artery occlusion model (MCAO) using C57BL/6J mice [152]. Accordingly, the applications of I. tenuifolia Pall ethanolic extract one hour before or immediately after the surgery outstandingly decreased the infarct size.…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…Thus, different volatile organic compounds classes have been recognized in the essential oils of this plant. These compounds belong to monoterpenes (141)(142)(143)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153), sesquiterpenes , diterpenes (179,180), triterpenes (181), fatty acids (182-197), aliphatic hydrocarbons (198-205), aldehydes (207-210) and cyclohexenones (211) (Table 5). Several studies have shown that essential oil (EO) from this plant is dominated by fatty acids regardless of the species and geographical origin, with various monomers as the major compounds.…”
Section: Essential Oilsmentioning
confidence: 99%
“…Iris species are also used as medicinal plants. Several pharmacological studies have shown that the rhizome extracts of Iris species have anticancer, anti-inflammatory, and α-glucosidase inhibitory effects and can reduce human infarct volume [5][6][7]. Few species are used to treat throat-swelling diseases [8].…”
Section: Introductionmentioning
confidence: 99%